Gender Difference in the Relationship of Physical Activity and Subjective Happiness Among Chinese University Students - Jiang, Wenning; Luo, Jin; Guan, Hannan (Frontiers in Psychology, 2021)
Background: Gender makes a difference in health and physical activity (PA). This research aimed to identify the gender difference in the relationship of PA and subjective happiness among Chinese health professions students. Methods: A cross-sectional survey was conducted in Shanghai Jiao Tong University from July 7 to 17 in 2021, using an anonymous online self-report questionnaire. The questionnaire included the Chinese version of the International Physical Activity Questionnaire-Short Form (IPAQ-SF), the Subjective Happiness Scale (SHS), the Depression Anxiety Stress Scale-21(DASS-21). The demographic and health-related factors were also reported. Findings: In total, 1512 health professions students (1108 males and 404 females) completed the survey. The SHS score was 17.20±3.44, and it was 17.00±3.23 in males, and 17.75±3.93 in females, respectively (p<0.001). There was no gender difference in vigorous, moderate PA, or walk, while female students have longer sedentary behavior hours/day than males. Male students scored higher in each subscale of DASS-21. Controlling for confounders, vigorous PA min/week and sedentary behavior hours/day were significantly associated with happiness in male students. In contrast, walk min/week was associated with happiness in female students. Interpretation: This research demonstrated a significant gender difference in the association between PA and happiness. Policymakers and college management should pay more attention to PA programs to promote students' happiness and mental health status.